Altered Topological Organization of Functional Brain Networks in Betel Quid Dependence: A Resting-State Functional MRI Study - Liu, Tao; Liu, Liting; Chen, Hui Juan; Fu, Qingqing; Fu, Lili; Huang, Weiyuan; Chen, Feng (Frontiers in Psychiatry, 2022)
Background: Betel quid dependence (BQD) is associated with abnormalities in the widespread inter-regional functional connectivity of the brain. However, no studies focused on the abnormalities in the topological organization of brain functional networks in chewers in Mainland China. Methods: In the current study, resting-state functional magnetic resonance images were acquired from 53 BQD individuals and 37 gender and age-matched healthy controls (HCs). A functional network was constructed by calculating the Pearson correlation coefficients among 90 subregions in the human Brainnetome Atlas. The topological parameters were compared between BQD individuals and HCs. Results: The results showed that BQD individuals presented the small-world topology but the normalized characteristic path length (λ) increased compared with HCs (0.563 ± 0.030 vs. 0.550 ± 0.027). Compared to HCs, BQ chewers showed increased betweenness centrality (Be) in the right supplementary motor area, right medial superior frontal gyrus, right paracentral lobule, right insula, left posterior cingulate gyrus, right hippocampus, right postcentral gyrus, right superior parietal gyrus and right supramarginal gyrus, while decreased Be was found in the orbitofrontal area and temporal area which is associated with reward network, cognitive system and default mode network. The AUC value of λ displayed a positive correlation with the duration of BQ chewing (r = 0.410, P = 0.002). Conclusions: The present study revealed the disruption of functional connectome in brain areas of BQD individuals. The findings may improve our understanding of the neural mechanism of BQD from a brain functional network topological organization perspective.